UMP HsKA Dual-Degree graduate, Mohammed Shafiq is active in sports - Siti Nurfarmy, Ibrahim (2019)
The programme of Bachelor of Engineering (Hons) Automotive Engineering, a collaboration programme with Karlsruhe University of Applied Science (HsKA), Germany, is often considered a rather difficult programme for some.